The Efforts in the Utilization of Village Funds and Their Challenges - ASRANI; Peribadi (Jurnal Neo Societal, 2025)
This study examines the utilization of Village Funds allocated by the government since 2015 to alleviate poverty in rural areas. Employing a qualitative approach with a participatory and case study design, the research observes the dynamics of Village Fund use across various villages. The findings reveal that the allocation of Village Funds remains predominantly directed toward physical infrastructure projects rather than socioeconomic empowerment programs. This focus on physical development has led to certain irregularities, including budget inflation for project costs. Additionally, the study identifies several obstacles, such as the limited capacity of village facilitators, which hinder the effective use of Village Funds. To enhance the quality and impact of Village Fund utilization, this study recommends improving facilitation capacity through more comprehensive training, strengthening the role of Community Empowerment Institutions (CEIs) in oversight, and implementing more targeted participatory development strategies. These recommendations aim to maximize the benefits of Village Funds in improving rural community welfare and reducing poverty rates.